SAWAR DARAH OTAK KARAKTERISTIK MOLEKULER DAN MODEL IN VITRO KULTUR PADA APARATUS TRANSWELL - Agatha Grace Muljono* (Neurona Majalah Kedokteran Neuro Sains, 2016)
ARE WHO WE ARE BECAUSE OF OUR BRAIN OUR CENTRAL NERVOUS SYSTEM THE BRAIN AND SPINAL CORD IS PROTECTED BY A COMPLEX STRUCTURE KNOWN AS THE BLOODBRAIN BARRIER BLOODBRAIN BARRIER IN SPITE OF ITS PROTECTIVE FUNCTION ALSO POSES AS AN OBSTACLE TOWARDS DRUG DEVELOPMENT TARGETING THE CENTRAL NERVOUS SYSTEM